2014
DOI: 10.1186/2193-1801-3-223
|View full text |Cite
|
Sign up to set email alerts
|

Are virtues national, supranational, or universal?

Abstract: Many studies investigated cultural differences in values, most notably by Hofstede and Schwarz. Relatively few have focused on virtues, a related and important concept in contemporary social science. The present paper examines the similarities and differences between nations, or blocks of - culturally related - nations on the perceived importance of virtues. Adults (N = 2.809 students) from 14 countries were asked to freely mention which virtues they found important to practice in daily life, and next to rate … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(6 citation statements)
references
References 11 publications
0
6
0
Order By: Relevance
“…An internal source of CSW is virtue (Coopersmith, 1967). Van Oudenhoven et al (2014, p. 2) define virtue as "morally good traits that everyone either may possess or can learn." Observing a moral code may lead people to feel higher self-worth (Solomon et al, 1991).…”
Section: Virtue Dimensionmentioning
confidence: 99%
See 2 more Smart Citations
“…An internal source of CSW is virtue (Coopersmith, 1967). Van Oudenhoven et al (2014, p. 2) define virtue as "morally good traits that everyone either may possess or can learn." Observing a moral code may lead people to feel higher self-worth (Solomon et al, 1991).…”
Section: Virtue Dimensionmentioning
confidence: 99%
“…Some virtues are important in specific nations, such as Goodness (generosity, altruism, courage and smartness), virtues that are frequently mentioned in France, but not in the Hispanic cluster (consisting of Chile) and Anglo-Saxon cluster (consisting of the US). Thus, France has a more distinctive national virtue pattern (Van Oudenhoven et al, 2014).…”
Section: Competitive Dimension Usmentioning
confidence: 99%
See 1 more Smart Citation
“…The importance ratings of virtues between the Northern and Southern European countries showed much larger differences than between Muslims and non-Muslims within the same country (van Oudenhoven et al 2012). Another study focused on cultural differences of virtues conducted in 14 countries also found strong evidence for correlations between blocks of culturally related nations and the perceived importance of numerous virtues (van Oudenhoven et al 2014). Hence, it is not so wrong to assume that the relativity of virtue meanings found in our study could be influenced by different sociocultural contexts under which individuals meaningfully shape and develop virtues as an integral part of themselves with the inevitable consequence of discrepancy in interpretations and understandings of some virtues.…”
Section: Discussionmentioning
confidence: 95%
“…6,9 Advances in fields of social-psychological research demonstrate that while general concepts of morality are universal, there are cross-national, sociocultural differences in the importance of virtues over time. 10 Additionally, it is important to realize that the various approaches to ethical decision-making are not mutually exclusive and often present as conflicting options. Therefore, when faced with a specific situation in practice, the pharmacist should contemplate all approaches in the decision-making process.…”
Section: Ethics Terminologymentioning
confidence: 99%